Gender and Responding to Rudeness: A Case Study of Iraqi EFL Learners - Abboodi Ali , Shurooq (Journal of College of Education, 2020)
Responding to rudeness is one of the speech acts that has been conducted by few researchers particularly on the eastern culture. This study aims to investigate the pragmatic behavior of Iraqi male and female EFL learners in situations where they experience rude behaviours. To this end, 60 participants divided equally into 30 males and 30 females have participated in this study. A discourse completion task (DCT) is used to elicit responses and a structured interview is conducted to support the analysis of data. Beebe and Waring’s (2005) coding scheme of responding to rudeness is adapted to code the data of this study. Qualitative and quantitative approaches are used in analysing the data. The findings unveil that these learners are mainly more aggressive in their responses to rudeness in addition to being more acquiescent than persistent. Both Iraqi genders use an identical number of strategies, but evident differences are revealed throughout the results. Iraqi males tend to use more aggressive strategies due to their nature of being conflictive and dominant in their interactions. As for Iraqi females, they prefer to use more acquiescent strategies due to their nature of being unproblematic and incompatible with aggression. Finally, some pedagogical implications for EFL teachers and learners are provided in this study.